The A-test – reliability of functional recovery assessment during early rehabilitation of patients in an orthopedic ward - Vukomanović, Aleksandra; Djurović, Aleksandar; Popović, Zoran; Ilić, Dejan (Vojnosanitetski pregled, 2014)
Background/Aim. There are few tests for evaluation of functional abilities of patients surgically treated for hip fractures or osteoarthritis during early rehabilition period. The aim of this study was to investigate reliability (interobserver reproducibility and internal consistency) of the A-test, an original test for functional recovery evaluation during early rehabilitation of patients in an orthopedic ward. Methods. The investigation included 105 patients (55 patients with hip osteoarthritis that underwent arthroplasty and 50 surgically treated patients with hip fracture). It was conducted in an orthopedic ward during early inpatient rehabilitation (from 1st to 5th day). For their functional recovery evaluation during early rehabilitation we used the A-test, a performance-based test with 10 items for assessing basic activities by six level ordinal scale (0–5). For internal consistency of the test the Cronbach coefficient alpha was calculated for the A-test results collected during early rehabilitation for all patients (105 patients x 5 days = 525 measures) and separately for the results of patients with hip osteoarthritis (275 measures) and hip fracture (250 measures). Values of this coefficient > 0.7 imply good internal consistency of the test. Interobserver reproducibility was estimated as follows: two physiotherapists together conducted physical therapy with the patients, and then, separately, rated the performance of each activity from the test (78 measures). The agreement between their estimations was expressed by the linear weighted kappa coefficient (for very good agreement values of kappa coefficeent have to be in the range 0.81–1). Results. The Cronbach coefficient alpha was 0.98 (the results of all the patients and the results of the patients with hip osteoarthritis) and 0.97 (the results of the patients with hip fracture). The values of kappa coefficient were in the range 0.81–0.92 for all items. Conclusion. The A-test is a reliable instrument for everyday evaluation of functional recovery during early rehabilitation of patients surgically treated in an orthopedic ward.
Keywords: hip fractures; osteoarthritis; hip; hip prosthesis; orthopedic procedures; postoperative period; physical therapy; recovery of function; predictive value of the tests